THE INFLUENCE OF PRICE, NEEDS AND LOCATION ON DECISIONS TO PURCHASE BEEF AT THE KRANGGAN JATISAMPURNA MARKET – BEKASI CITY - Dion Dharmajaya; Suadi Sapta Putra; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to determine the influence of price, needs and location on beef purchasing decisions at Kranggan Jatisampurna Market - Bekasi City. This research was carried out because there were price issues in the market which created problems in the field resulting in instability of sales in the market, then there were changes in the level of people's needs for beef consumption which made purchasing decisions have to be faced by consumers and also the location at Kranggan Jatisampurna Market - Bekasi City also becomes part of consumer purchasing decisions. The population used in this research is all consumers who are shopping or purchasing beef at the Kranggan Jatisampurna Market - Bekasi City. The sampling technique uses probability sampling with a simple random sampling method, namely taking samples freely without looking at the consumer's status. To determine the sample size, use the formula from Hair et. al, where the results were 108 respondents. The test results in the research show that price has no significant effect on the decision to purchase beef, then need has a positive and significant effect on the decision to purchase beef and also location has a positive and significant effect on the decision to purchase beef.